The temple and the community in Qumran and the New Testament: a comparative study in the temple symbolism of the Qumran texts and the New Testament - Gärtner, Bertil Edgar (Society for New Testament Studies monograph series, 1965)
This is the first of a series of monograph supplements to the journal New Testament Studies. The main purpose of the series is to make possible publication of work which is too long for inclusion in the journal. The monographs will be published in either English, French or German: the present one is in English. Dr Gärtner's purpose is to follow in detail the parallels between the New Testament and Qumran writings in their concpet of the community - Christian or Essene - as a spiritual temple. The whole complex of relationships between Qumran and the early Church is studied with the purpose of extending our knowledge of the Jewish background of the New Testament. Dr Gärtner's conclusions lend strong support to the view that it is from this Qumran type of Judaism that the Christian Church arose.